Polyester film and application thereof
The laminated film with tailored optical and mechanical properties addresses image distortion and structural issues in foldable displays, enhancing mass production and portability by preventing creases and cracks.
Patent Information
- Application Number
- JP2024165242
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-05-28
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-05-07
AI Technical Summary
Conventional foldable displays suffer from image distortion and structural issues such as creases or cracks at the folded portions due to repeated folding, which affects mass production and device functionality.
A laminated film with specific refractive index ranges (1.590-1.620 in the bending direction, 1.670-1.700 in the folded part, 1.520 or less in the thickness direction, and a density of 1.380g/cm³) and elastic modulus (2.7 GPa or less in the bending direction, 4.5 GPa or more in the folded portion) is used to enhance the durability and flexibility of foldable displays.
The laminated film maintains image quality without distortion and prevents cracks, ensuring high mass productivity and improved portability of foldable displays in mobile devices.
Smart Images

Figure 2024178952000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate film for a foldable display, a foldable display, and a mobile terminal device, and more particularly to a foldable display and a mobile terminal device that are less susceptible to image distortion due to film deformation even when repeatedly folded, and a laminate film that can provide the foldable display. [Background technology]
[0002] As mobile terminal devices become thinner and lighter, smartphones and other mobile terminal devices are becoming more and more popular. While mobile terminal devices are required to have a variety of functions, they are also required to be convenient. For this reason, the mobile terminal devices that are currently in use must be able to perform simple operations with one hand, and must have a small screen size of around 6 inches, since they are assumed to be stored in a pocket or similar.
[0003] On the other hand, tablet devices with screen sizes of 7 to 10 inches are highly functional and can be used not only for video content and music, but also for business purposes, drawing, reading, etc. However, they cannot be operated with one hand, are less portable, and have issues with convenience.
[0004] To achieve these goals, a method has been proposed of connecting multiple displays together to make them more compact (see Patent Document 1), but this method has not become widespread because it leaves a bezel, which means the image is cut off and visibility is reduced.
[0005] In recent years, mobile terminals incorporating flexible displays and foldable displays have been proposed, which provide a large-screen display without interruption to the image and are convenient to carry around.
[0006] Here, in the case of conventional displays and mobile terminal devices that do not have a folding structure, the surface of the display can be protected by a non-flexible material such as glass, but in the case of a folding display, when a one-sided display is formed through a folding part, it is necessary to use a hard coat film that is flexible and can protect the surface. However, in a folding display, the part corresponding to a certain folding part is repeatedly folded, so that the film in that part deforms over time, causing problems such as distorting the image displayed on the display. In addition to the surface protection film, films are used in various parts of the folding display, such as polarizing plates, retardation plates, touch panel substrates, substrates of display cells such as organic EL, and protective members on the back surface, and durability against repeated folding is also required for these films.
[0007] In view of this, a method has been proposed in which the film thickness is partially changed (see Patent Document 2), but this method has the problem of being poorly suited for mass production.
[0008] A method of adjusting the refractive index in the bending direction of a polyester film has also been proposed (see Patent Document 3), but as the refractive index in the bending direction is reduced, the pencil hardness when a hard coat is applied decreases, resulting in a problem of reduced surface protection function for displays. In addition, lowering the refractive index in one direction improves deformation when folded, but increases uniaxial orientation in the folding direction, resulting in problems such as cracks or breakage at the folded portion. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2010-228391 A [Patent Document 2] JP 2016-155124 A [Patent Document 3] International Publication No. 2018 / 150940 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention seeks to solve the problems associated with conventional display components as described above, and aims to provide a foldable display that is easy to mass-produce and has no risk of distortion of the image displayed at the folded portion after repeated folding, and a laminate film for a foldable display that does not produce fold marks or cracks at the folded portion, in order to provide a mobile terminal device equipped with such a foldable display. [Means for solving the problem]
[0011] That is, the present invention comprises the following: 1. A laminate film for a folding display, comprising a polyester film having a thickness of 10 to 80 μm, a hard coat layer on one side of the polyester film, and an adhesive layer on the side of the polyester film opposite to the side having the hard coat layer, wherein the polyester film satisfies the following conditions: (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) Refractive index in the thickness direction is 1.520 or less (4) Density is 1.380 g / cm 3 End (Here, the bending direction refers to the direction perpendicular to the fold when folding the polyester film.) 2. A laminate film for a folding display as described in 1 above, wherein the elastic modulus of the polyester film in the bending direction is 2.7 GPa or less and the elastic modulus in the direction of the fold is 4.5 GPa or more. 3. The laminate film for a folding display according to the above 1 or 2, wherein the adhesive layer has a thickness of 1 to 50 μm. 4. The laminate film for a foldable display according to any one of the above 1 to 3, wherein the hard coat layer has a thickness of 1 to 50 μm. 5. A foldable display in which the laminate film for a foldable display described above in any one of 1 to 4 is arranged as a surface protective film so that the hard coat layer is positioned on the surface, and a continuous single laminate film is arranged through the folding portion of the foldable display. 6. A mobile terminal device having the foldable display described in claim 5. Effect of the Invention
[0012] A foldable display using the laminate film for foldable displays of the present invention maintains mass productivity, while the laminate film does not develop cracks at the folding portion, does not deform after repeated folding, and does not cause image distortion at the folding portion of the display. A mobile terminal device equipped with a foldable display using such a laminate film provides beautiful images, is highly functional, and is convenient in terms of portability, etc. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic diagram showing the bending radius when the foldable display of the present invention is folded. [Diagram 2] FIG. 2 is a schematic diagram showing the bending direction of a polyester film constituting the laminate film for a foldable display in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] (display) The display in the present invention generally refers to a display device, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc., but LCD, organic EL, and inorganic EL having a bendable structure are preferred. In particular, organic EL and inorganic EL, which can reduce the layer structure, are more preferred, and organic EL, which has a wide color gamut, is even more preferred.
[0015] (Foldable display) A folding display is a continuous display that can be folded in half or the like when carried. By folding, the size can be halved, improving portability. The bending radius of the folding display is preferably 5 mm or less, more preferably 3 mm or less. If the bending radius is 5 mm or less, it can be made thin when folded. It can be said that the smaller the bending radius, the better, but the smaller the bending radius, the easier it is to leave creases. The bending radius is preferably 0.1 mm or more, but may be 0.5 mm or more, or may be 1 mm or more. Even if the bending radius is 1 mm, it is possible to achieve a practically sufficient thinness when carried. The bending radius when folded is measured at the location of the symbol 11 in the schematic diagram of FIG. 1, and means the inner radius of the folded part when folded. The surface protection film, which is one application of the laminated film of the present invention described later, may be located on the outside or inside of the folded folding display. Furthermore, the foldable display may be folded in three or four, or may be a rollable type, all of which are considered to fall within the scope of the foldable display of the present invention.
[0016] The laminate film for folding displays of the present invention may be used in any part of a folding display as long as it is a component of the folding display. Below, a typical configuration of a folding display and the part in which the laminate film of the present invention can be used are described using an organic EL display as an example. Hereinafter, the laminate film for folding displays of the present invention may be simply referred to as the laminate film of the present invention.
[0017] (Foldable OLED display) The essential component of a folding organic EL display is an organic EL module, and further includes a circular polarizing plate, a touch panel module, a front protective film, a back protective film, and the like, as required. (Organic LED module) The general structure of an organic EL module is composed of an electrode / electron transport layer / light-emitting layer / hole transport layer / transparent electrode.
[0018] (Touch panel module) It is preferable that the mobile terminal device has a touch panel. When an organic EL display is used, it is preferable that a touch panel module is disposed on the top of the organic EL display or between the organic EL module and the circular polarizer. The touch panel module has a transparent substrate such as a film and a transparent electrode disposed thereon. The laminated film of the present invention can be used as this transparent substrate. When used as a transparent substrate for a touch panel, it is preferable to provide a refractive index adjustment layer.
[0019] (Circular polarizing plate) A circular polarizing plate suppresses deterioration of image quality due to reflection of external light by members inside a display. A circular polarizing plate has a linear polarizing plate and a retardation plate. A linear polarizing plate has a protective film on at least the viewing side surface of a polarizer. A protective film may also be provided on the surface opposite to the viewing side of the polarizer, or a retardation plate may be directly laminated on the polarizer. The retardation plate is a resin film having a retardation such as polycarbonate or cyclic olefin, or a resin film provided with a retardation layer made of a liquid crystal compound. The laminated film of the present invention can be used as a polarizer protective film. In these cases, when the base film of the laminated film of the present invention is a polyester film, it is preferable that the slow axis direction of the polyester film is parallel or perpendicular to the absorption axis direction of the polarizer. A deviation of 10 degrees, preferably 5 degrees, from this parallel or perpendicular direction is allowed.
[0020] (Surface protection film) When an impact is applied to a display from above, the circuits of an organic EL module or a touch panel module may be broken, so a surface protective film is often provided. The laminated film of the present invention is used as this surface protective film. Surface protective films include those called cover windows that are incorporated into the outermost surface of a display, and those called afters that can be attached, peeled off, and replaced by the user himself, but the laminated film of the present invention is used in either case. The hard coat layer is provided on the surface of a folding display with the hard coat layer on the viewing side. The hard coat layer may be provided on both sides.
[0021] (Back protection film) It is also preferable that a protective film is provided on the back side of the display, and the laminated film of the present invention can be used as the protective film on the back side.
[0022] The laminate film of the present invention may be any other film than those described above, so long as it is used in a portion of a folding display that is folded. Among these, the laminated film of the present invention is preferably used as a cover window surface protective film, an after-surface protective film, a base film of a touch panel module, or a back surface protective film, and more preferably used as a cover window surface protective film or an after-surface protective film.
[0023] In addition, the laminate film of the present invention does not necessarily have to be used for all of the above applications as a folding display. In the folding display, a laminate film having a base material such as a polyester film, a polyimide film, a polyamide film, a polyamideimide film, a polycarbonate film, an acrylic film, a triacetyl cellulose film, a cycloolefin polymer film, a polyphenylene sulfide film, or a polymethylpentene film can be used appropriately according to suitability.
[0024] When the base film constituting the laminated film of the present invention is a polyester film, it may be a single-layer film made of one or more types of polyester resin, or when two or more types of polyester are used, it may be a multilayer structure film or an ultra-multilayer laminate film with a repeating structure.
[0025] Examples of polyester resins used in the polyester film, which is the base film of the laminated film, include polyester films made of polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, or copolymers mainly composed of the constituent components of these resins. Among these, stretched polyethylene terephthalate films are particularly preferred in terms of mechanical properties, heat resistance, transparency, cost, etc.
[0026] When a polyester copolymer is used for the polyester film, which is the base film of the laminated film, examples of the dicarboxylic acid component of the polyester include aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid; and polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. Examples of the glycol component include fatty acid glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol; aromatic glycols such as p-xylene glycol; alicyclic glycols such as 1,4-cyclohexanedimethanol; and polyethylene glycols having an average molecular weight of 150 to 20,000. The mass ratio of the copolymerization components of the preferred copolymer is less than 20% by mass. When it is less than 20% by mass, the film strength, transparency, and heat resistance are maintained, which is preferable.
[0027] In addition, in the production of polyester film, which is the base film of the laminated film, the intrinsic viscosity of at least one type of resin pellet is preferably in the range of 0.50 to 1.0 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, the impact resistance of the obtained film is improved, and disconnection of the internal circuit of the display due to external impact is less likely to occur, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the filtration pressure of the molten fluid does not increase too much, which makes it easier to operate the film production stably, which is preferable.
[0028] The thickness of the polyester film, which is the base film of the laminated film, is preferably 10 to 80 μm, and more preferably 25 to 75 μm. A thickness of 10 μm or more improves the pencil hardness and impact resistance, while a thickness of 80 μm or less is advantageous for weight reduction and is excellent in flexibility, processability, handleability, etc.
[0029] The surface of the laminated film of the present invention may be smooth or uneven, but since it is used for covering the surface of a display, it is not preferable for the optical properties to be deteriorated due to the unevenness. The haze is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower limit of the haze is preferably 0.1% or more from the viewpoint of stable production, but it may be 0.3% or more.
[0030] As described above, in order to reduce haze, it is preferable that the unevenness of the film surface is not too large. However, in order to provide a certain degree of slipperiness from the viewpoint of ease of handling, unevenness can be formed by blending particles into the base polyester film or by coating the base polyester film with a coating layer containing particles during the film formation process.
[0031] The method of blending particles into the base polyester film can be a known method. For example, it can be added at any stage of polyester production, but preferably it can be added as a slurry dispersed in ethylene glycol or the like at the stage of esterification, or after the completion of transesterification reaction and before the start of polycondensation reaction, and polycondensation reaction can be carried out. It can also be carried out by a method of blending a slurry of particles dispersed in ethylene glycol or water with polyester raw material using a vented kneading extruder, or a method of blending dried particles with polyester raw material using a kneading extruder.
[0032] Among them, a method is preferred in which aggregated inorganic particles are homogeneously dispersed in a monomer liquid that will become a part of the polyester raw material, and then the filtered product is added to the remainder of the polyester raw material before, during, or after the esterification reaction. According to this method, since the monomer liquid has a low viscosity, homogeneous dispersion of the particles and highly accurate filtration of the slurry can be easily performed, and when added to the remainder of the raw material, the dispersibility of the particles is good and new aggregates are unlikely to be generated. From this viewpoint, it is particularly preferred to add to the remainder of the raw material in a low temperature state before the esterification reaction.
[0033] In addition, the number of protrusions on the film surface can be further reduced by a method in which, after obtaining a polyester containing particles in advance, the pellets are mixed and extruded with pellets not containing particles (master batch method).
[0034] The polyester film substrate may contain various additives, such as antistatic agents, UV absorbers, and stabilizers, within a range that maintains a preferred range of total light transmittance.
[0035] The total light transmittance of the polyester film as the base material is preferably 85% or more, more preferably 87% or more. With a transmittance of 85% or more, visibility can be sufficiently ensured. The total light transmittance of the polyester film as the base material is preferably 85% or more in order to increase the total light transmittance of the laminated film. Although it can be said that the higher the total light transmittance of the polyester film, it is preferable that it is 99% or less from the viewpoint of stable production, and may be 97% or less.
[0036] The maximum heat shrinkage of the polyester film substrate after heat treatment at 150°C for 30 minutes is preferably 6% or less, more preferably 5% or less. A heat shrinkage of 6% or less can suppress flatness defects such as curling and undulation during HC processing. The lower the heat shrinkage, the better, but it is preferably -1% or more, and more preferably 0% or more. The negative value here means that the film expanded after heating, and flatness defects may occur if the value is less than -1%.
[0037] In order to provide the laminated film for folding displays of the present invention with sufficient pencil hardness, it is preferable that the polyester film, which is the base film, has the following properties. It is considered that, in the conventional base polyester film, after laminating a hard coat layer, in the pencil hardness evaluation of the hard coat film (laminated film), the film is deformed in the thickness direction, which causes the pencil hardness to decrease. In the present invention, it is preferable to set the indentation depth after unloading the test force in the thickness direction of the base polyester film using a dynamic ultra-microhardness meter described later to a specific range. In the pencil hardness evaluation of the hard coat film using the above-mentioned base polyester film, it is preferable that a high hardness can be achieved. The indentation depth in the thickness direction of the base polyester film after unloading the test force is preferably 1.5 μm or less, more preferably 1.4 μm or less, and even more preferably 1.3 μm or less. If the indentation depth after unloading the test force (final deformation amount when a load is applied) is 1.5 μm or less, in the pencil hardness evaluation of the hard coat film (laminated film) after laminating the hard coat layer, the film is less likely to deform in the thickness direction, and the pencil hardness can be increased. If the pencil hardness of the hard coat film (laminated film) can be increased, scratches and dents are less likely to occur on the display surface, improving the visibility of the display. The lower the indentation depth after the test force is removed, the better, but from the viewpoints of stable production and saturation of the effect, a depth of 0.3 μm or more is preferable, and even more preferable is 0.5 μm or more.
[0038] In order to reduce the indentation depth after the test force is removed, it is effective to adjust the refractive index in the thickness direction to 1.520 or less. As a means for adjusting the refractive index to 1.520 or less, as described later, examples of the means include setting conditions such as adjusting the stretch ratio in the bending direction or folding direction to a high value, setting the stretching temperature in the bending direction or folding direction to a low value, and setting the heat setting temperature to a high value, within a range in which other physical properties and the refractive index in the bending direction or folding direction can be controlled to a preferred range.
[0039] The elastic modulus of the polyester film in the bending direction, which is the substrate, is preferably 2.7 GPa or less, more preferably 2.6 GPa or less, and even more preferably 2.5 GPa or less. By reducing the elastic modulus in the bending direction, the stress applied to the hard coat layer when the hard coat film (laminated film) is bent can be reduced. It can be said that the lower the elastic modulus in the bending direction, the better the bending property, but since the flatness of the display surface is impaired, 1.8 GPa or more is preferable. The elastic modulus in the folding direction is preferably 4.5 GPa or more, more preferably 4.6 GPa or more, and even more preferably 4.7 GPa or more. By increasing the elastic modulus in the folding direction, the flatness of the display surface can be maintained when the display is produced. The higher the elastic modulus in the folding direction, the more preferable it is, but from the viewpoint of film formability, 8.0 GPa or less is preferable.
[0040] The polyester film described above can be produced, for example, through a polymerization step in which inorganic particles are homogeneously dispersed in a monomer liquid that becomes a part of the polyester raw material, the dispersion is filtered, and then the dispersion is added to the remainder of the polyester raw material to polymerize the polyester, and a film formation step in which the polyester is melt-extruded through a filter into a sheet, which is cooled and stretched to form a base film.
[0041] Next, a method for producing a polyester film as a substrate will be described in detail using an example in which polyethylene terephthalate (hereinafter, sometimes referred to as PET) pellets are used as the raw material for the substrate film, but the present invention is not limited to this. In addition, the number of layers, such as a single layer structure or a multilayer structure, is not limited.
[0042] After mixing and drying PET pellets in a predetermined ratio, the mixture is fed to a known melt lamination extruder, extruded from a slit die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of a single layer, one extruder is sufficient, but in the case of producing a film with a multilayer structure, two or more extruders, two or more manifolds or merging blocks (e.g., merging blocks having a rectangular merging portion) are used to laminate multiple film layers constituting each outermost layer, and a sheet of two or more layers is extruded from a die and cooled on a casting roll to form an unstretched film.
[0043] In this case, it is preferable to perform high-precision filtration to remove foreign matter contained in the resin at any location where the molten resin is kept at about 280° C. during melt extrusion. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a filter material made of sintered stainless steel is preferable because it has excellent performance in removing aggregates and high-melting organic matter mainly composed of Si, Ti, Sb, Ge, and Cu.
[0044] Furthermore, the filtration particle size (initial filtration efficiency 95%) of the filter medium is preferably 20 μm or less, particularly preferably 15 μm or less. If the filtration particle size (initial filtration efficiency 95%) of the filter medium exceeds 20 μm, foreign matter with a size of 20 μm or more cannot be sufficiently removed. By using a filter medium with a filtration particle size (initial filtration efficiency 95%) of 20 μm or less to perform high-precision filtration of molten resin, productivity may decrease, but it is preferable to obtain a film with few protrusions due to coarse particles.
[0045] (Refractive index in bending direction) In the present invention, the refractive index of at least one of the longitudinal direction (machine flow direction) and the width direction of the polyester film as the base material is preferably 1.590 to 1.620, more preferably 1.591 to 1.600. The refractive index of the bending direction of the polyester film is preferably 1.590 to 1.620, more preferably 1.591 to 1.600. Here, the bending direction refers to the direction perpendicular to the folding part (reference number 21) assumed in the use of a folding display, as shown by reference number 22 on the polyester film (reference number 2) in FIG. 2. When the refractive index of at least one of the longitudinal direction and the width direction is 1.590 to 1.620, there is little deformation when repeatedly folded, and there is no risk of deteriorating the image quality of the folding display, which is preferable. The refractive index is more preferably 1.591 to 1.600. Of course, the direction is preferably the bending direction. If the refractive index is 1.590 or more, there is no risk of cracks occurring in the folded portion direction after the bending test described below, and of course no breakage occurs, so that the visibility of the display can be maintained good. The refractive index of the polyester film can be effectively adjusted by adjusting the stretching ratio and stretching temperature. In addition, a relaxation process in the stretching direction and multi-stage stretching may be used to adjust the refractive index. When multi-stage stretching is performed, it is preferable to make the stretching ratios in the second and subsequent stages higher than the stretching ratio in the first stage.
[0046] By controlling the refractive index in at least one of the longitudinal direction (machine flow direction) and the width direction of the polyester film within the above range, and more preferably by controlling the refractive index in the bending direction within the above range, fatigue due to the compressive stress applied to the inside of the fold when folded can be reduced. It is believed that fatigue due to compressive stress occurs mainly in the crystalline portion, and fatigue is less likely to occur when there are fewer crystals in the bending direction. Therefore, it is believed that by lowering the refractive index, the amount of oriented crystals in the bending direction is reduced, and compression fatigue is suppressed.
[0047] Furthermore, the creep phenomenon caused by tensile stress applied to the outside of the fold when the material is folded can be suppressed by reducing the refractive index. Fatigue caused by tensile stress is thought to occur mainly in the amorphous portion, and the repeated application of stress causes molecular chains to align, resulting in deformation. It can be assumed that the fewer molecular chains aligned in the bending direction, the less deformation caused by alignment. Furthermore, since fatigue caused by tension can be suppressed with fewer amorphous portions, a higher degree of crystallinity, i.e., a higher density, is preferable.
[0048] In the present invention, the stretching ratio of the unstretched polyester sheet in at least one of the longitudinal direction (machine flow direction) and the width direction is preferably 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. The stretching direction is preferably the bending direction. A stretching ratio of 1.2 times or more is preferable because there is no deformation during post-processing such as hard coat coating, and a stretching ratio of 2.0 times or less is preferable because thickness unevenness of the film does not occur. The stretching temperature is preferably 75 to 120°C, more preferably 75 to 105°C. The heating method during stretching can be a conventionally known method such as hot air heating method, roll heating method, and infrared heating method. By setting the stretching temperature to 75 to 120°C, it is possible to prevent large thickness unevenness due to stretching at the above stretching ratio. In addition, by stretching at a temperature as low as possible within a range in which large thickness unevenness does not occur as described above, the refractive index in the thickness direction can be reduced.
[0049] (Refractive index in the direction of the fold) The refractive index in the direction perpendicular to the direction in which the refractive index of the polyester film as the base material is 1.590 to 1.620 is preferably 1.670 to 1.700. That is, the refractive index in the direction perpendicular to the bending direction (direction of the folded portion) is preferably 1.670 to 1.700. By making it 1.670 to 1.700, deformation when folded in the bending direction can be reduced. By making it 1.700 or less, cracks and breaks in the direction of the folded portion can be suppressed. By making it 1.670 or more, the flexibility in the bending direction can be improved and the surface hardness can be improved. 1.680 to 1.695 is more preferable. Methods for adjusting the refractive index in the direction perpendicular to the bending direction include the stretching ratio, stretching preheating temperature, stretching temperature, multi-stage stretching, and film relaxation. The stretching ratio is preferably 4.0 to 6.0 times, more preferably 4.4 to 6.0 times. The preheating temperature for stretching in the direction perpendicular to the bending direction is preferably 70 to 110° C. When multi-stage stretching is performed in the direction perpendicular to the bending direction, it is preferable to set the stretch ratio higher in the second and subsequent stages than in the first stage. The film may be relaxed by 1 to 10% in either the machine flow direction (longitudinal direction) or the perpendicular direction (width direction).
[0050] (Refractive index in the thickness direction) The refractive index in the thickness direction of the polyester film serving as the substrate is preferably 1.520 or less. More preferably, it is 1.515 or less, even more preferably 1.510 or less, particularly preferably 1.505 or less, and most preferably 1.500 or less. By making it 1.520 or less, even if the refractive index in the bending direction is designed to be low, the decrease in hardness of the film surface can be suppressed, and both flexibility and surface hardness can be achieved. By making it 1.520 or less, the indentation depth after unloading the test force in the thickness direction is reduced, and the hardness of the film surface, particularly the pencil hardness of the hard coat film after lamination of the hard coat layer, can be improved. The refractive index in the thickness direction is preferably low, but from the viewpoint of stable production, it is preferably 1.3 or more, and may even be 1.4 or more. Particularly preferably, it is 1.410 or more. It can be said that the above range can be achieved by increasing the stretch ratio in both the bending direction and the folding direction, but in order to control the refractive index in the thickness direction after controlling the refractive index in the bending direction and the width direction to a preferred range, it is preferable to set the conditions while checking the balance of the conditions of each process in the film formation process.
[0051] The method of controlling the refractive index in the thickness direction of the polyester film as the substrate within the above range includes the preheating temperature, stretching temperature, and stretching ratio in the bending direction, the preheating temperature, stretching temperature, multi-stage stretching, high-ratio stretching, or heat fixing temperature setting in the bending direction. The preheating temperature in the bending direction is preferably 70°C to 110°C. The stretching temperature in the bending direction is preferably 75°C to 120°C. The stretching ratio in the bending direction is preferably 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. By lowering the stretching temperature and stretching at a low stretching ratio, the refractive index in the thickness direction can be effectively reduced while maintaining the flexibility in the bending direction. The preheating temperature in the folding direction is also preferably 75°C to 110°C. The stretching temperature is preferably 75°C to 120°C. The stretching ratio in the folding direction is preferably 4.0 to 6.0 times, more preferably 4.4 to 6.0 times. The refractive index in the thickness direction can be effectively reduced while maintaining or reducing the refractive index in the bending direction. Multi-stage stretching may be used as a method of high-ratio stretching. In this case, it is preferable to set the stretching ratio in the second stage higher than that in the first stage, since the refractive index can be effectively controlled. A method of stretching again after the crystallization step may also be used. Accelerated stretching may also be used, in which the stretching speed is increased from the initial stage to the latter stage of stretching. The heat setting temperature is preferably 180 to 240° C. By carrying out heat setting, oriented crystallization in the stretching direction advances, and the refractive index in the thickness direction can be reduced. The reason why lowering the refractive index in the thickness direction improves the hardness of the film surface is not entirely clear, but it is thought that aromatic groups such as benzene rings in the molecular chain are oriented in the plane direction, which has the effect of suppressing deformation due to stress applied in the thickness direction.
[0052] (Regarding density of polyester film) The density of the polyester film substrate is 1.380g / cm 3 It is preferable that the density is 1.383 g / cm or more. 3 More preferably, it is 1.380 g / cm or more. 3By setting the density to 1.40 g / cm or more, it is possible to improve the flexibility and the film surface hardness, particularly the pencil hardness of the hard coat film after laminating the hard coat layer. The higher the density, the better. Although it depends somewhat on the presence or absence of particles in the film, it is preferable to set the density to 1.40 g / cm or more. 3 By setting the heat setting temperature during film formation to 180 to 240° C., crystallization can be promoted and the density can be effectively increased.
[0053] The bending direction of the polyester film as the substrate is preferably set to correspond to the longitudinal direction (machine flow direction). This makes it easier to reduce the refractive index in the bending direction by biaxial stretching and improve the flexibility. That is, a polyester film is preferably obtained by stretching an unstretched polyester sheet in the longitudinal direction at a stretching ratio of 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. In addition, it can be said that a preferred embodiment is to stretch the polyester sheet in the transverse direction at a stretching ratio of 4.0 to 6.0 times, more preferably 4.4 to 6.0 times.
[0054] In the laminated film of the present invention, the polyester film as the substrate is (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) Refractive index in the thickness direction is 1.520 or less (4) Density is 1.380 g / cm 3 End It is particularly preferable to have the above four characteristics simultaneously, but even if the combination is within the above-mentioned preferred manufacturing conditions, it may not necessarily be possible to obtain a film that satisfies all four characteristics simultaneously if the combination is not the best within each preferred manufacturing condition range, for example, a combination of a stretch ratio in the bending direction of 1.4 times or less, a stretch ratio in the folding direction of less than 4.4 times, and a heat setting temperature of 220° C. or less. In this case, the above four characteristics can be simultaneously satisfied by fine-tuning any of the conditions or a combination of them, such as increasing the stretch ratio in the bending direction to 1.7 times or more, increasing the stretch ratio in the folding direction to 4.4 times or more, increasing the heat setting temperature to about 230° C., or lowering the stretching temperature in the bending direction and / or the folding direction.
[0055] In order to adjust the film formability, film strength, thermal dimensional stability, and appearance defects, any film forming method such as stretching, relaxation, heat setting, and surface treatment may be used, but it can be said that a particularly preferred embodiment of the present invention is to control the refractive index and density of the polyester film substrate within the above-mentioned preferred ranges. By controlling the refractive index and density within the preferred ranges, it is possible to provide a polyester film suitable for a folding display, which has superior bending resistance and surface hardness compared to conventional films, particularly high pencil hardness of the hard coat film after laminating a hard coat layer.
[0056] Specifically, for example, PET pellets are thoroughly vacuum-dried, then fed to an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to form an unstretched PET sheet. The unstretched sheet obtained is stretched 1.2 to 2.0 times, more preferably 1.7 to 2.0 times, in the longitudinal direction with a roll heated to 75 to 120°C to obtain a uniaxially oriented PET film. Furthermore, the end of the film is held by a clip and introduced into a hot air zone heated to 75 to 120°C, and after drying, is stretched 4.0 to 6.0 times, more preferably 4.4 to 6.0 times, in the transverse direction. Subsequently, the film can be introduced into a heat treatment zone at 180 to 240°C and heat-treated for 1 to 60 seconds. During this heat treatment process, a relaxation treatment of 0 to 10% may be performed in the transverse or longitudinal direction as necessary.
[0057] The intrinsic viscosity of the polyester film substrate is preferably in the range of 0.50 to 1.0 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, the impact resistance is improved and disconnection of the internal circuit of the display due to external impact is less likely to occur, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the increase in the filtration pressure of the molten fluid is not too large, which is preferable because film production is stable.
[0058] (Easy adhesion layer) In the present invention, in order to improve the adhesion between the polyester film as the substrate and the adhesive layer or hard coat layer, it is also preferable to laminate an easy-adhesion layer on the polyester film. The easy-adhesion layer can be obtained by applying a coating liquid for forming the easy-adhesion layer to one or both sides of an unstretched or uniaxially stretched film in the longitudinal direction, heat-treating and drying as necessary, and then stretching the film in at least one direction that is not stretched. Heat treatment can also be performed after biaxial stretching. The final coating amount of the easy-adhesion layer is 0.005 to 0.20 g / m 2 It is preferable to control the coating amount to 0.005 g / m 2 On the other hand, if the coating amount is 0.20 g / m or more, adhesiveness is obtained, which is preferable. 2 If it is not more than this, blocking resistance can be obtained, which is preferable.
[0059] Resins contained in the coating liquid used for laminating the easy-adhesion layer can be, for example, polyester resins, polyether polyurethane resins, polyester polyurethane resins, polycarbonate polyurethane resins, acrylic resins, etc., and can be used without particular limitation. Examples of crosslinking agents contained in the coating liquid for forming the easy-adhesion layer include melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, etc. Two or more of each can also be mixed and used. Due to the nature of in-line coating, these are preferably applied using a water-based coating liquid, and the resins and crosslinking agents are preferably water-soluble or water-dispersible resins or compounds.
[0060] It is preferable to add particles to the easy-adhesion layer to give it easy slipperiness. The average particle size of the fine particles is preferably 2 μm or less. If the average particle size of the particles exceeds 2 μm, the particles are likely to fall off from the easy-adhesion layer. Examples of particles to be contained in the easy-adhesion layer include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be added to the easy-adhesion layer alone, or two or more types may be added in combination.
[0061] The coating liquid can be applied by a known method, similar to the coating layer described above, such as reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating, which can be used alone or in combination.
[0062] (Hard coat layer) When the laminated film of the present invention is used as a surface protection film for protecting a folding display by placing it on the surface of the display, it is preferable that the hard coat layer is provided on at least one surface of the polyester film as a substrate. The hard coat layer is preferably placed on the display surface side of the polyester film and used in the display. In order to suppress curling, the hard coat layer may be provided on both sides. As the resin for forming the hard coat layer, acrylic, siloxane, inorganic hybrid, urethane acrylate, polyester acrylate, epoxy, etc. can be used without any particular limitation. In addition, two or more types of materials can be mixed and used, and particles such as inorganic filler and organic filler can be added.
[0063] (Thickness of hard coat layer) The thickness of the hard coat layer is preferably 1 to 50 μm. If the thickness is 1 μm or more, it is preferable because it is cured sufficiently and has a high pencil hardness. Furthermore, if the thickness is 50 μm or less, curling due to cure shrinkage of the hard coat can be suppressed, and the handling properties of the film can be improved.
[0064] (Application method) The hard coat layer can be applied by any method including, but not limited to, a Mayer bar, a gravure coater, a die coater, a knife coater, etc., and can be appropriately selected depending on the viscosity and film thickness.
[0065] (Curing conditions) The hard coat layer can be cured by energy rays such as ultraviolet rays and electron beams, or by heat, and is preferably cured by ultraviolet rays or electron beams in order to reduce damage to the film.
[0066] (Pencil hardness) The pencil hardness of the hard coat layer is preferably 3H or more, more preferably 4H or more. If the hard coat layer has a pencil hardness of 3H or more, it is not easily scratched and does not reduce visibility. In general, the pencil hardness of the hard coat layer is preferably high, but it may be 9H or less, 8H or less, or even 6H or less can be used without any practical problems.
[0067] (Properties of laminated film) The hard coat layer in the present invention can be used for the purpose of protecting a display by increasing the pencil hardness of the surface as described above, and preferably has a high transmittance. The total light transmittance of the laminated film is preferably 85% or more, more preferably 88% or more. If the transmittance is 85% or more, sufficient visibility can be obtained. The total light transmittance of the laminated film is generally preferably as high as possible, but from the viewpoint of stable production, it is preferably 99% or less, and may be 97% or less. In addition, the haze of the laminated film is generally preferably low, and preferably 3% or less. The haze of the laminated film is more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower the haze, the better, but from the viewpoint of stable production, it is preferably 0.1% or more, and may be 0.3% or more.
[0068] The hard coat layer may further have other functions added thereto. For example, the hard coat layer having the above-mentioned functions such as an antiglare layer having a certain pencil hardness, an antiglare antireflection layer, an antireflection layer, a low reflection layer, an antiscratch layer, and an antistatic layer are preferably used in the present invention.
[0069] A hard coat layer may also be provided when used as a substrate film of a touch panel module. When an ITO layer is used as a transparent electrode layer of a touch panel module, for example, a refractive index adjustment layer is preferably provided between the substrate film and the transparent electrode layer to make the electrode pattern less visible. In this case, the hard coat layer itself may also serve as a refractive index adjustment layer, or a separate layer for refractive index adjustment may be laminated.
[0070] (Adhesive layer) It is preferable that the laminated film has an adhesive layer on the opposite side to the side having the hard coat layer of the polyester film, which is the base material of the laminated film. The material constituting the adhesive layer is not particularly limited, and for example, conventional adhesives such as rubber-based, acrylic-based, and polyolefin-based adhesives can be used. Examples of rubber-based adhesives include natural rubber, butadiene rubber, isoprene rubber, and the like, as well as styrene-based block copolymer elastomers such as SBS, SIS, SEBS, and SEPS. Examples of acrylic-based adhesives include crosslinked copolymers such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Examples of crosslinking agents include isocyanate compounds, epoxy compounds, metal chelating agents, and compounds containing multiple double bonds. Examples of polyolefin-based adhesives include ethylene-propylene rubbers such as EPM and EPDM, those in which these are used as soft segments and polyethylene or polypropylene are used as hard segments, and blends of ethylene-propylene rubber with polyethylene or polypropylene. The adhesiveness can be adjusted by adding a known tackifier, softener, etc. to the adhesive layer. The adhesiveness can also be adjusted by adjusting the molecular weight of the base polymer used. The adhesive layer may further contain other components. Examples of other components include additives (i.e., auxiliaries), such as dyes, pigments, antistatic agents, antioxidants, light stabilizers, ultraviolet absorbers, neutralizing agents, nucleating agents, epoxy stabilizers, lubricants, antibacterial agents, flame retardants, plasticizers, etc.
[0071] (Adhesive layer thickness) The thickness of the adhesive layer is from 1 μm to 50 μm, preferably from 2 μm to 40 μm, and more preferably from 4 μm to 30 μm.
[0072] (Coating method) An adhesive solution is applied and dried, or in the case of acrylic-based materials, a monomer or oligomer is applied, followed by radiation curing or the like, or a substrate-less optical adhesive sheet (OCA) may be transferred.
[0073] It is preferable to change the adhesive strength (peel strength) depending on the material to which it is attached. In a folding display, if the adhesive strength is weak, the problem of the bent part floating will occur, so the adhesive strength with glass after 24 hours is preferably 10 to 40 N / 25 mm.
[0074] A release film may be provided on the surface of the adhesive layer (the surface opposite to the polyester film).
[0075] (Release film) As the release film for the pressure-sensitive adhesive sheet, any film that is widely used as a release film can be appropriately used. The resin of the base film is not particularly limited, and any resin film such as polyester, polycarbonate, polyamide, polyimide, polyamideimide, polystyrene, triacetyl cellulose, polypropylene, and cyclic polyolefin can be used without limitation. Among these, polyester is preferred from the standpoint of mechanical strength, heat resistance, supply stability, and the like, and polyethylene terephthalate is more preferred. In addition, the film may be an unstretched film or a stretched film. In the case of a stretched film, it may be a uniaxially stretched film or a biaxially stretched film. Among these, a biaxially stretched polyethylene terephthalate film is preferred.
[0076] When the base film itself has releasability, it can be used as a release film as it is. In order to adjust the releasability, the base film may be subjected to a surface treatment such as a corona treatment, a plasma treatment, or a flame treatment.
[0077] (Release layer) Furthermore, the base film may be provided with a release layer. Examples of the release layer include silicone-based, amino resin-based, alkyd resin-based, long-chain acrylic resin-based, etc., and the composition and type can be appropriately selected according to the required release force.
[0078] When a release layer is provided, an easy-adhesion layer may be provided on the base film. As the easy-adhesion layer, a layer that has been conventionally used in each base film such as a polyester-based, acrylic-based, or polyurethane-based layer can be used, and can be selected according to the base film and release layer to be used.
[0079] (Antistatic layer) The release film may have an antistatic layer. Examples of the antistatic agent for the release layer include quaternary ammonium salts, conductive polymers such as polyaniline and polythiophene, needle-shaped metal fillers, conductive high refractive index fine particles such as tin-doped indium oxide fine particles and antimony-doped tin oxide fine particles, and combinations of these. The binder resin may be polyester, polyurethane, polyamide, acrylic, etc. The antistatic layer is provided on the release surface and may exist as an underlayer of the release layer, or may be provided on the side opposite to the release surface. EXAMPLES
[0080] Next, the present invention will be described with reference to examples and comparative examples. First, the evaluation methods of the characteristic values carried out in the present invention will be described below.
[0081] (1) Intrinsic viscosity of polyester Polyester film or polyester resin was crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). After the solution was centrifuged to remove inorganic particles, the flow time of a solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of the solvent alone were measured using an Ubbelohde viscometer, and the intrinsic viscosity was calculated from the ratio of these times using the Huggins equation and assuming that the Huggins constant is 0.38.
[0082] (2) Bending resistance of polyester film sample (bending radius 1.5 mm) A polyester film sample with a size of 20 mm in the width direction × 110 mm in the flow direction is prepared. Using a no-load U-shaped stretch tester (Yuasa System Co., Ltd., DLDMLH-FS), the bending radius is set to 1.5 mm, and the sample is bent 200,000 times at a speed of 1 time / second. At that time, the sample is fixed at a position 10 mm from both ends of the long side, and the bending portion is 20 mm × 90 mm. Here, FIG. 1 is a schematic diagram for showing the bending radius when a folding display is folded, and considering the case where a polyester film is arranged on the inner surface of the folded state, a bending test is performed as a model with the portion indicated by the symbol 11 in FIG. 1 set to 1.5 mm. After the bending process, the sample was placed on a flat surface with the inner side of the bend facing down, and visual observation was performed. ○: No cracks or deformations were observed in the sample. ×: The sample had a crack or crease, and when placed horizontally, the maximum floating height was 5 mm or more.
[0083] (3) Bending resistance of laminated film sample (bending radius 3.0 mm) Using the same method as in the bending test described above, the hard-coated film was bent 200,000 times at a bending radius of 3.0 mm and a speed of 1 bend / second. When there was only one hard-coated layer, tests were performed with the hard-coated layer on the inside and on the outside, respectively. ◯: No cracks were found in the hard coat layer, and no deformation was observed in the hard coat film. ×: Broken, or cracks were observed in the hard coat layer, or deformation was observed in the hard coat film.
[0084] (4) Refractive index of polyester film In accordance with JIS K 7142:2014 "Measurement method for refractive index of plastics (Method A)", the refractive index in the longitudinal direction, width direction, and thickness direction was determined using an Abbe refractometer (Atago Co., Ltd., NAR-4T, measurement wavelength 589 nm).
[0085] (5)Pencil hardness Using a laminated film as a sample, the measurement was performed in accordance with JIS K 5600-5-4: 1999, with a load of 750 g and a speed of 1.0 mm / s. In the present invention, a value of 3H or more was considered to be acceptable.
[0086] (6) Total light transmittance, haze The haze was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries Co., Ltd.).
[0087] (7) Density The density was measured according to the method compliant with JIS K 7112:1999 (density gradient tube method). (Unit: g / cm 3 ).
[0088] (8) Indentation depth after removing the test force The sample was cut into approximately 2 cm squares and fixed on a micro cover glass 18 × 18 mm (manufactured by Matsunami Glass Co., Ltd.) with an adhesive (Cemedine (registered trademark) High Super 30) on the surface opposite to the measurement surface. After adhesion and fixing, it was left at room temperature for 12 hours or more, and then the indentation depth (μm) after removing the test force was measured using a dynamic ultra-microhardness tester "DUH-211" (manufactured by Shimadzu Corporation) under the following conditions. <Measurement conditions> Test mode: Load-unload test Indenter used: Triangular pyramidal indenter with ridge angle of 115 degrees Indenter elastic modulus: 1.140×106N / mm 2 Indenter Poisson's ratio: 0.07 Test force: 50mN Load speed: 4.44mN / sec Load holding time: 2sec Unloading holding time: 0sec
[0089] (9) Maximum heat shrinkage rate The sample film was cut to 10 mm length x 250 mm width, and marks were made at 200 mm intervals along the long side in the direction to be measured, and the mark interval A was measured under a constant tension of 5 g. The sample film was then left in an oven at 150°C for 30 minutes without load, and then removed from the oven and cooled to room temperature. The mark interval B was then measured under a constant tension of 5 g, and the heat shrinkage rate (%) was calculated using the following formula. The heat shrinkage rate was measured at three equal positions in the width direction of the sample film, and the average value of the three points was taken as the heat shrinkage rate (%). Heat shrinkage rate (%) = [(AB) x 100] / A The sample film is cut so that the length and width of the sample differ in both the bending direction and the folding direction, and measurements are taken. The data in the direction where the measured value is greater is regarded as the maximum heat shrinkage rate (%).
[0090] (10) Tensile modulus (Young's modulus (unit: GPa)) The tensile modulus of elasticity in the bending direction and the folding direction of the polyester film was measured at 23° C. in accordance with JIS K7127:1999.
[0091] (Preparation of polyethylene terephthalate pellets (a)) A continuous esterification reactor consisting of a three-stage complete mixing tank having an agitator, a partial condenser, a raw material inlet, and a product outlet was used as the esterification reactor, and the slurry was continuously fed to the first esterification reactor of the esterification reactor with TPA at 2 tons / hr, EG at 2 moles per mole of TPA, and antimony trioxide at an amount such that Sb atoms were 160 ppm relative to the produced PET, and reacted at normal pressure for an average residence time of 4 hours at 255°C. Next, the reaction product in the first esterification reactor was continuously taken out of the system and fed to the second esterification reactor, and EG distilled from the first esterification reactor was fed to the second esterification reactor at 8% by mass relative to the produced polymer (produced PET), and further, an EG solution containing magnesium acetate in an amount such that Mg atoms were 65 ppm relative to the produced PET and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET were added, and reacted at normal pressure for an average residence time of 1.5 hours at 260°C. Next, the reaction product in the second esterification reactor was continuously taken out of the system and fed to a third esterification reactor, and an EG solution containing TMPA in an amount such that the P atom was 20 ppm relative to the produced PET was added, and the reaction was carried out at normal pressure for an average residence time of 0.5 hours at 260° C. The esterification reaction product produced in the third esterification reactor was continuously fed to a three-stage continuous polycondensation reactor to carry out polycondensation, and further filtered with a stainless steel sintered filter medium (nominal filtration accuracy of 90% cut of 5 μm particles) to obtain polyethylene terephthalate pellets (a) with an intrinsic viscosity of 0.62 dl / g.
[0092] (Preparation of polyethylene terephthalate pellets (b)) In the same manner as in the production process of polyethylene terephthalate pellets (a), except for adjusting the residence time of the third esterification reaction, the intrinsic viscosity was adjusted to 0.580 dl / g to obtain polyethylene terephthalate pellets (b).
[0093] (Preparation of polyethylene terephthalate pellets (c)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (c) having an intrinsic viscosity of 0.75 dl / g.
[0094] (Polymerization of urethane resin) A four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer was charged with 72.96 parts by mass of 1,3-bis(isocyanate methyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol having a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as a solvent, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, the reaction liquid was cooled to 40°C, and then 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C. While stirring and mixing at 2000 min-1, an isocyanate group-terminated prepolymer was added and dispersed in water. Thereafter, acetonitrile and a portion of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35 mass %.
[0095] (Polymerization of Water-soluble Carbodiimide Compounds) In a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, a dropping funnel, and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phospholene-1-oxide as a carbodiimide catalyst were added, and the mixture was stirred for 10 hours at 180°C under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Next, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100°C for 24 hours. Water was gradually added to the mixture at 50°C to obtain a yellow, transparent, water-soluble carbodiimide compound (B) with a solid content of 40% by mass.
[0096] (Preparation of Coating Solution for Forming Adhesion Layer) The following coating materials were mixed to prepare a coating solution. Water 16.97 parts by mass Isopropanol 21.96 parts by weight Polyurethane resin (A) 3.27 parts by weight Water-soluble carbodiimide compound (B) 1.22 parts by mass Particles 0.51 parts by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant 0.05 parts by weight (Silicone-based, solids concentration 100% by mass)
[0097] (Preparation of hard coat coating solution a) 0.1 parts by mass of a leveling agent (BYK307, manufactured by BYK Japan, concentration 100%) was added to 100 parts by mass of a hard coat material (Opstar (registered trademark) Z7503, manufactured by JSR Corporation, concentration 75%), and the mixture was diluted with methyl ethyl ketone to prepare a hard coat coating solution a with a solid content concentration of 40% by mass.
[0098] (Preparation of hard coat coating solution b) 95 parts by mass of pentaerythritol triacrylate (A-TMM-3, manufactured by Shin-Nakamura Chemical Co., Ltd., solid content concentration 100%), 5 parts by mass of a photopolymerization initiator (Irgacure (registered trademark) 907, manufactured by BASF Japan, solid content concentration 100%), and 0.1 parts by mass of a leveling agent (BYK307, manufactured by BYK Japan, solid content concentration 100%) were mixed and diluted with a solvent of toluene / MEK=1 / 1 to prepare a hard coat coating solution b with a concentration of 40% by mass.
[0099] Example 1 Pellets of polyethylene terephthalate (a) were fed to an extruder and melted at 285°C. The polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10μm particles 95% cut), extruded from a die in the form of a sheet, and then contacted with a casting drum with a surface temperature of 30°C using an electrostatic casting method to cool and solidify, producing an unstretched film. The unstretched film was uniformly heated to 75°C using a heating roll, heated to 85°C using a non-contact heater, and roll-stretched (longitudinal stretching) 1.4 times. The above-mentioned coating solution for forming an easy-adhesion layer was applied to both sides of the obtained uniaxially stretched film by a roll coating method, and then dried at 80°C for 20 seconds. The coating amount after the final (biaxial stretching) drying was 0.06g / m 2 The film was then introduced into a tenter, preheated at 105°C, transversely stretched 4.0 times at 95°C, fixed in width, heat-set at 230°C for 5 seconds, and further relaxed in the width direction by 4% at 180°C to obtain a polyethylene terephthalate film with a thickness of 50 μm. One side of the prepared film was coated with hard coat coating solution a using a Mayer bar so that the film thickness after drying would be 5 μm, and the film was dried at 80°C for 1 minute, and then irradiated with ultraviolet light (accumulated light amount 200 mJ / cm2). 2 ), a hard coat film was obtained. Then, a double-sided adhesive sheet (manufactured by Lintec Corporation, product name "OPTERIA MO-3006C", thickness: 25 μm) was attached to the side of the polyethylene terephthalate film on which the hard coat layer was not laminated, to obtain a laminated film. The evaluation results are shown in Table 1.
[0100] (Examples 2 to 3) A polyester film was obtained in the same manner as in Example 1 except that the longitudinal stretching ratio was changed to that shown in Table 1, and a laminated film was obtained.
[0101] Example 4 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the width direction was changed to 4.4 times and the heat setting temperature was changed to 220° C., and then a laminated film was obtained.
[0102] (Examples 5 to 6) A polyester film was obtained in the same manner as in Example 4 except that the stretching ratio in the longitudinal direction was changed as shown in Table 1, and a laminated film was obtained.
[0103] Example 7 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the width direction was changed to 5.5 times and the heat setting temperature was changed to 190° C., and then a laminated film was obtained.
[0104] (Examples 8 to 9) A polyester film was obtained in the same manner as in Example 7 except that the stretching ratio in the longitudinal direction was changed as shown in Table 1, and a laminated film was obtained.
[0105] Example 10 A polyester film was obtained and a laminated film was obtained in the same manner as in Example 5, except that in the production process of Example 5, after the film was stretched in the longitudinal direction, a 10% relaxation heat treatment was performed at 100° C.
[0106] Example 11 In the manufacturing process of Example 5, the clips were released at 200°C after heat setting, and relaxation heat treatment was performed in the longitudinal and width directions, but otherwise the same procedure was followed as in Example 5 to obtain a polyester film and a laminated film. The tenter speed and the winding roll speed were adjusted so that the relaxation rate in the longitudinal direction was 3%. The relaxation in the width direction was left in a free state.
[0107] Example 12 A polyester film was obtained in the same manner as in Example 1, except that the temperature during longitudinal stretching was changed to 75°C and the heat setting temperature was changed to 220°C, and then a laminated film was obtained.
[0108] Example 13 A polyester film was obtained in the same manner as in Example 1, except that the temperature during longitudinal stretching was changed to 75°C, the stretching ratio was changed to 1.2 times, and then the stretching ratio was changed to 5.0 times in the width direction, and a laminated film was obtained.
[0109] Example 14 A polyester film was obtained in the same manner as in Example 3, except that the longitudinal stretching in Example 3 was a two-stage stretching in which the stretching ratio in the first stage was 1.2 times and the stretching ratio in the second stage was 1.67 times, and a laminated film was obtained. The total longitudinal stretching ratio was about 2.0 times.
[0110] Example 15 A polyester film was obtained in the same manner as in Example 5, except that the preheating temperature during widthwise stretching was changed to 95°C and the heat setting temperature was changed to 190°C, and then a laminated film was obtained.
[0111] Example 16 A polyester film was obtained in the same manner as in Example 2, except that the stretching in the width direction in Example 2 was changed to two-stage stretching, the stretching ratio in the first stage was 1.5 times, the stretching ratio in the second stage was 4.0 times, and the heat setting temperature was changed to 190° C., and then a laminated film was obtained. The total stretching ratio in the width direction was 6.0 times.
[0112] (Examples 17 to 18) A polyester film was obtained in the same manner as in Example 2 except that the thickness was changed as shown in Table 1, and a laminated film was obtained.
[0113] (Example 19) A polyester film was obtained in the same manner as in Example 1, except that the relaxation heat treatment in the width direction was not carried out in the production process of Example 1, and then a laminated film was obtained.
[0114] (Example 20) An unstretched film was prepared in the same manner as in Example 1, and the unstretched film was preheated at 75°C in a tenter and stretched laterally to 1.4 times at 85°C. The above-mentioned coating liquid for forming an easy-adhesion layer was applied to both sides of the obtained uniaxially stretched film by roll coating, and then dried at 80°C for 20 seconds. The final coating amount after drying (after biaxial stretching) was 0.06 g / m 2The film was uniformly heated to 105°C using a heating roll, heated to 95°C using a non-contact heater, and roll-stretched (longitudinal stretching) at 4.0 times the original size. The film was fixed in width and heat-set at 230°C for 5 seconds to obtain a polyethylene terephthalate film with a thickness of 50 μm. The subsequent steps were the same as in Example 1 to obtain a laminated film.
[0115] Example 21 A polyethylene terephthalate film having a thickness of 50 μm was obtained in the same manner as in Example 1, and then a hard coat film was obtained by coating the hard coat coating solution b. Thereafter, a laminate film was obtained in the same manner as in Example 1.
[0116] Comparative Example 1 A polyester film was obtained in the same manner as in Example 1, except that the film was not stretched in the longitudinal direction but was stretched only in the width direction, that is, uniaxially stretched in the transverse direction, to obtain a laminated film.
[0117] Comparative Example 2 A polyester film was obtained in the same manner as in Example 7, except that the film was not stretched in the longitudinal direction but was stretched only in the width direction, that is, uniaxially stretched in the transverse direction, to obtain a laminated film.
[0118] (Comparative Examples 3 to 7) A polyester film was obtained in the same manner as in Example 1, except that the heat setting temperature was changed to 220° C., and the PET pellets and thickness were as shown in Table 1, and then a laminate film was obtained. As described above, in Comparative Examples 3 to 7, the heat setting temperature was lower than that in Example 1, and the combination of the longitudinal and transverse stretching ratios was not the best within the preferable range of conditions. As shown in Table 1, the refractive index in the thickness direction increased, the indentation depth after the test force was removed was large, and the pencil hardness after the hard coat layer was laminated was smaller than that in each Example.
[0119] Comparative Example 8 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction was changed to 2.7 times and the heat setting temperature was changed to 220° C., and then a laminated film was obtained.
[0120] Comparative Example 9 A polyester film was obtained in the same manner as in Example 1 except that the stretching ratio in the longitudinal direction was changed to 3.4 times, and then a laminated film was obtained.
[0121] Comparative Example 10 A polyester film was obtained in the same manner as in Example 4 except that the heat setting temperature was changed to 100° C., and then a laminated film was obtained.
[0122] Comparative Example 11 A polyester film was obtained in the same manner as in Example 13 except that the longitudinal stretching temperature was changed to 130° C., and then a laminated film was obtained.
[0123] Comparative Example 12 A polyester film was obtained in the same manner as in Example 1 except that the preheating temperature in the width direction was changed to 120° C., and then a laminated film was obtained.
[0124] The laminated film was attached to the organic EL module via a 25 μm thick adhesive layer, and a smartphone-type folding display that can be folded in half at the center of the entire display with a radius of 3 mm, which corresponds to the bending radius in FIG. 1, was created. The laminated film was arranged on the surface of one continuous display through the folding part, and the hard coat layer was arranged so as to be located on the surface of the display. The laminated film of each example was used to satisfy the operation and visibility as a smartphone that can be folded in half at the center and carried around. In addition, the surface was not dented by external force. On the other hand, the folding display using the laminated film of each comparative example seemed to cause image distortion at the folding part of the display as the frequency of use increased, which was not very preferable. In addition, some of the displays had dents and scratches on the surface.
[0125] [Table 1] [Industrial Applicability]
[0126] A foldable display using the laminate film for a foldable display of the present invention maintains mass productivity, and since the laminate film located on the surface of the foldable display does not deform after repeated folding, no image distortion occurs at the folded portion of the display. In particular, a mobile terminal device or image display device equipped with a foldable display using the laminate film of the present invention as a surface protective film provides beautiful images, is highly functional, and has excellent convenience such as portability. [Explanation of symbols]
[0127] 1: Foldable display 11: Bending radius 2: Polyester film substrate that constitutes the laminated film for foldable displays 21: Folding section 22: Bending direction (direction perpendicular to the folding part)
Claims
1. A polyester film having a hard coat layer on one side thereof, A laminate film for a folding display, comprising a polyester film having an adhesive layer on a surface opposite to a surface having a hard coat layer, the polyester film satisfying the following conditions: (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) A refractive index in the thickness direction is 1.520 or less. (4) Density is 1.380 g / cm 3 End (5) The polyester film is a biaxially oriented polyethylene terephthalate film. (Here, the bending direction refers to the direction perpendicular to the fold when folding the polyester film.)
2. 2. The laminate film for a folding display according to claim 1, wherein the polyester film has an elastic modulus of 2.7 GPa or less in the bending direction and an elastic modulus of 4.5 GPa or more in the direction of the folded portion.
3. A laminated film for a foldable display as described in claim 1 or 2, having a thickness of 10 to 80 μm and a thickness of the adhesive layer of 1 to 50 μm.
4. The laminate film for folding displays according to any one of claims 1 to 3, wherein the hard coat layer has a thickness of 1 to 50 µm.
5. A foldable display in which the laminate film for a foldable display according to any one of claims 1 to 4 is arranged as a surface protective film so that the hard coat layer is positioned on the surface, and a continuous single laminate film is arranged through the folding portion of the foldable display.
6. A mobile terminal device comprising the foldable display according to claim 5.
Citation Information
Patent Citations
Easily adhesive polyester film for optical use
JP2014065887A
Folding display and mobile terminal device
JP2018072663A
Polyester film and applications thereof
WO2018150940A1
Polyester film as surface protective film for foldable display and application thereof
WO2018159285A1
Method of processing hard coat film, hard coat film and protective film
JP2010228391A
